Perceived Brand Personality of Symbolic Brands - MÜLLER, RE-AN (Journal of Economics and Behavioral Studies, 2014)
Brand personality can be defined as a set of human characteristics associated with a brand (Aaker, 1997).This study reports on the perceived brand personality of symbolic brands as seen by Generation Y students from one higher education institution campus located in South Africa. The respondents were asked to write down the first brand that came to mind for eight symbolic product categories. The top two brands in each category were used in a self-administered questionnaire. A second group of respondents were then asked to write down personality traits they associate with each of the identified brands. These findings, present a unique viewpoint regarding a number of brands and how the respondents perceive their brand personalities.